Bullying and Its Prevention Among Intensive Care Nurses. Issue 6 (7th October 2015) - Ganz, Freda DeKeyser; Levy, Hadassa; Khalaila, Rabia; Arad, Dana; Bennaroch, Kochav; Kolpak, Orly; Drori, Yardena; Benbinishty, Julie; Raanan, Ofra
Abstract: Purpose: International studies report that nurse bullying is a common occurrence. The intensive care unit (ICU) is known for its high stress levels, one factor thought to increase bullying. No studies were found that investigated bullying in this population. The purpose of this study was to describe the prevalence of ICU nurse bullying and what measures were taken to prevent bullying. Design: This was a descriptive study of a convenience sample of 156 ICU nurses from five medical centers in Israel. Data collection was conducted over a 10‐month period in 2012 and 2013. Methods: After ethical approval, three questionnaires (background characteristics, Negative Acts Questionnaire‐Revised, and Prevention of Bullying Questionnaire) were administered according to unit preference. Descriptive statistics were calculated for all responses and a Pearson product moment correlation was calculated to determine the relationship between bullying and its prevention. Findings: Most of the nurses in the study were married, female staff nurses with a baccalaureate in nursing. No participant responded that they had been bullied daily, but 29% reported that they were a victim of bullying. The mean bullying score was 1.6 ± 1.4 out of 5. The mean prevention score was 2.4 ± 0.3 out of 4. Significant differences were found between hospitals on bullying, F (4, 155) = 2.7, p = .039, and between hospitals, F (4, 155) = 2.9, p = .026, and units, F (5, 143) = 3.4, p = .006, on prevention. The Prevention Scale significantly correlated with the bullying scale ( r = .58, p < .001). No other variables were found to be associated with either bullying or prevention scores. Conclusions: An alarming percentage of nurses were victims of bullying. Levels of bullying were low to moderate. Level of prevention was weak or moderate. The higher the level of bullying, the lower the level of prevention. The work environment as opposed to individual characteristics seems to have an impact on bullying and its prevention. Clinical Relevance: More measures must be taken to prevent bullying. Nurses must be educated to accept only a zero tolerance to bullying and to report bullying when confronted by bullying.